Manajemen School Branding dalam Meningkatkan Daya Saing Sekolah - Heni Maria Astutik; Taufiq Harris; Suyitno Suyitno; Heni Maria Astutik; Taufiq Harris; Suyitno Suyitno (Jurnal Riset Madrasah Ibtidaiyah, 2026)
This study aims to analyze school branding management in enhancing the competitiveness of an Islamic primary school. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation, and subsequently analyzed using the interactive model of Miles and Huberman. The findings reveal that school branding is managed through the integration of the school’s vision, flagship programs, school culture, and institutional communication strategies. Branding functions not merely as a promotional tool, but as a differentiation strategy that fosters trust and stakeholder engagement. School culture plays a fundamental role as the foundation of brand identity, strengthening the institutional image in a sustainable manner. The theoretical contribution of this study emphasizes that school branding in Islamic primary schools is most effective when grounded in values, consistency of educational services, and authentic student experiences. Practically, these findings offer a strategic framework for school administrators in designing branding initiatives aligned with academic quality and institutional character.